Tours to the Chernobyl zone as a phenomenon of dark tourism development - Romanova, Anna A. (Journal of the Belarusian State University. Economics, 2018)
The definition of the dark tourism has been proposed in the article. The components of dark tourism are presented, such as: disaster tourism, mystical tourism, tombstone tourism, death tours. The research of the dark tourism spectrum has been done. The definition of Chernobyl tourism has been given, as well as the classification of study tours to the exclusion zone as dark tourism (and not as extreme tourism) has been proved. The educational, recreational, economic and image functions of the Chernobyl tourism have been determined and analyzed. The peculiarities of Chernobyl tourism have een researched, such as: uniqueness; formation of a unique tourist product; self-organization; dominance of specialized tour operators; semi-legal status of tourist trips; rapid growth of popularity; increase in the number of illegal tourists («stalkers»); the predominance of foreign tourists; lack of developed tourism infrastructure and check-point regime; acts of vandalism in the exclusion zone; creation of souvenirs, cards and computer games on relevant topics; high interest of foreign investors etc. The emergence and development of a new type of tourism, such as Chernobyl tourism in the context of dark tourism, must be taken into account for effective strategic planning as well as a more thorough analysis of the functioning of the tourism industry. Recommendations for the safe, sustainable and economically justified tourism development in the Chernobyl zone  ave been suggested in the conclusions.
Keywords: dark tourism; Chernobyl tourism; extreme tourism; tourism industry; Chernobyl zone